REVIEW ON CONFIGURATION OF POWER SPLIT HYBRID ELECTRIC VEHICLES (Journal of Pharmaceutical Negative Results, 2023)
The hybrid powertrain is one of the most important technologies that have been developed to satisfy the challenging of fuel economy and emission standards. As is well known, a suitable configuration should not only meet the requirements of vehicle kinematics and dynamics, but also meet the requirement of fuel economy and emission. paper reviews the advances of EVs regarding battery technology trends. More specifically, an analysis of the worldwide market situation of EVs and their future prospects is carried out. In this paper, the hybrid powertrain system is regarded as a system with multiple power sources. Moreover, as well as the power control and battery energy management proposals